European dimension of education (EDE) - Mercè Berengueras Pont; José María Vera Mur (ADIDE Federación, 2016)
The communication aims to analyze the European dimension of education, in its current context, taking into account genesis and evolution. Its conceptual and legal framework is analyzed and its historical development and its limitations, concluding with their projections and future challenges. Communication complements the legal and regulatory references European level, issued by the European Council and education ministers, exposed and mentioned along communication.